Stutent’s Individuality within the Framework of Innovative Physical Education . - V. A. Salnikov; Y. M. Revenko; S. Y. Bebinov (Образование и наука)
The paper looks at the necessity of developing a new person- oriented paradigm of physical education, which involves a transition from the normative approach to sport-oriented one in training children, adolescents and young adults; compliance of educational means, forms, methods and conditions with the student’s psychological peculiarities; and sport specialization according to personal inclinations and abilities. The research subject is defined as the physically active personality development with the reference to psychological and age peculiarities. The aim of the study is to update the existing physical education system according to the demands for its health promoting and preserving functions. The methodology compiles the systematic and person-oriented approaches. Personal characteristics of students choosing different kinds of sports for physical education are described along with the correlation between their individual qualities and specificity of physical development. The research findings can be used in developing the curricula for physical education on different levels.